Transformasi Kecerdasan Pemimpin dalam Mengembangkan Pendidikan Islam di MAN 1 Nganjuk - A Wathon; Abd Aziz; Nur Efendi (Lembaga Yasin AlSys, 2025)
Although transformational leadership has been widely examined in previous research, studies that specifically highlight the transformation of leaders’ intelligence in the context of developing Islamic education in state madrasah remain limited. This study aimed to analyze how leadership intelligence at MA Negeri 1 Nganjuk is transformed and implemented to promote innovation and improve the quality of Islamic education. A qualitative approach with a case study design was employed, with data collected through in-depth interviews, participant observation, and document analysis at MA Negeri 1 Nganjuk. The findings show that the principal proactively develops strategic, emotional, spiritual, and digital intelligence, which contributes significantly to strengthening organizational culture, improving teacher performance, and enhancing the quality of learning for santri. These findings contribute to the development of Islamic educational leadership theory and broaden understanding of the role of adaptive intelligence in responding to contemporary challenges. The study concludes that developing holistic intelligence is crucial for madrasah leaders in the context of Islamic education and suggests that Kementerian Agama facilitate professional development programs focused on these aspects. The implications of this research include theoretical contributions to enriching the literature on transformational leadership in madrasah settings, practical implications for policymakers and education practitioners in designing more comprehensive leadership development strategies, and opportunities for further studies on the impact of collective intelligence and shared leadership within the madrasah ecosystem.